Effects of foreign and domestic central bank government bond purchases in a small open economy DSGE model: Evidence from Sweden before and during the coronavirus pandemic - Yildiz Akkaya; Carl-Johan Belfrage; Paola Di Casola; Ingvar Strid (Sveriges Riksbank, 2023)
This paper evaluates the macroeconomic effects of foreign and domestic central bank government bond purchases on the Swedish economy before and during the Corona pandemic using a small open economy DSGE model with segmented asset markets. In this model, the effects of foreign and domestic quantitative easing on the Swedish economy occur mainly through the exchange rate channel. The calibrated model is able to broadly capture the movements in foreign and domestic bond yields, capital flows and the Krona exchange rate associated with QE since the global financial crisis in 2007-2009. We find that foreign quantitative easing strengthened the Krona exchange rate and had modestly negative effects on Swedish GDP and inflation. Domestic QE, on the other hand, depreciated the Krona and had modestly positive macroeconomic effects. In 2015-2019 the government bond purchases on average depreciated the Krona by 2.5 percent, increased GDP by 0.2 percent, and increased inflation by 0.2 percentage points. The government bond purchases following the pandemic, which were more limited in size, had roughly half of these effects.
Keywords: E44; E52; F41; 330; Unconventional Monetary Policy; Quantitative Easing; Effective Lower Bound; International Spillovers; DSGE model